Volatility and Stability of ESG Equity in Indonesia toward Internal and External Shocks - Indra Gunawan; Muhammad Firdaus; Hermanto Siregar; Mulya E. Siregar (International Journal of Islamic Economics and Finance (IJIEF), 2022)
The Environmental, Social and Governance (ESG) index is rising in popularity globally especially in Indonesia. This study attempts to prove that ESG equity is less volatile than non-ESG equity, since specific components of ESG are essentially parts of the Shariah values. Using data from 2009 through 2020, the Vector Error Correction Model (VECM) method was utilized to further investigate the link between ESG and other endogenous variables such as the DJIM (Dow Jones Islamic Market), Fed rate, JCI (Jakarta Composite Index) index, exchange rate, and BI rate. The results show that all internal and external variables significantly influence ESG equity in very low magnitude, except for DJIM negatively and Fed rate positively. However, the IRF findings reveal what transpired to the ESG equity, which was able to endure shocks from both internal and external simultaneously, and to stabilize more swiftly. Moreover, the FEVD results shows that all internal and external variables have little impact to ESG equity totaling less than 9 per cent. Meanwhile, the impact of the same variables to non-ESG equity, i.e., JCI and DJIM, are higher at 38 per cent and 13 per cent, respectively. In addition, ESG equity tends to have a dominant influence on other non-ESG equity. Therefore, the Indonesian stock market will be more stable if ethical investing norms, such as ESG equity, are followed, which will be more judicious in order to achieve long-term growth.